2010
DOI: 10.1128/jvi.02265-09
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Hepatitis C Virus Envelope Evolution in Humans Is Consistent with Progressive Humoral Immune Selection during the Transition from Acute to Chronic Infection

Abstract: During the transition from acute to chronic infection in individuals persistently infected with hepatitis C virus (HCV), cellular responses initiate within the first 6 months of primary infection and collapse thereafter, whereas humoral responses activate later during the chronic phase. Whether and how this deviation of immune responses specifically influences HCV evolution are unknown. To determine the pattern of HCV evolution during this critical period, we conducted extensive sequence analysis on annual clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 62 publications
5
81
1
Order By: Relevance
“…We previously demonstrated that the evolutionary dynamics of HCV during early infection predicts the outcome of acute hepatitis C, such that a decrease in viral diversity correlates with viral clearance whereas an increase correlates with progression to chronicity (11). These data, subsequently corroborated elsewhere (12)(13)(14), are consistent with the concept that aspects of viral evolution reflect the strength of virus-specific adaptive immune responses and therefore the ability of the host to control the virus (8,15). However, little is known about the correlations among adaptive immunity, HCV evolution, and rates of disease progression once chronic hepatitis C is established.…”
supporting
confidence: 69%
“…We previously demonstrated that the evolutionary dynamics of HCV during early infection predicts the outcome of acute hepatitis C, such that a decrease in viral diversity correlates with viral clearance whereas an increase correlates with progression to chronicity (11). These data, subsequently corroborated elsewhere (12)(13)(14), are consistent with the concept that aspects of viral evolution reflect the strength of virus-specific adaptive immune responses and therefore the ability of the host to control the virus (8,15). However, little is known about the correlations among adaptive immunity, HCV evolution, and rates of disease progression once chronic hepatitis C is established.…”
supporting
confidence: 69%
“…The use of retroviral pseudoparticles bearing autologous HCV glycoproteins (HCVpp) from the initial inoculum allowed the precise examination of strain-specific neutralization. The late phase of chronic infection is accompanied by the induction of NAb responses as well as an increasing rate of envelope viral sequence evolution (106), indicative of ongoing humoral selection pressure. Viral escape may occur through several additional mechanisms (108), including an impaired cross-neutralizing activity that selects the outgrowth of viral variants and the interplay of HCV glycoproteins with HDL and the scavenger receptor SR-BI ( Figure 1A), which can prevent the effect of NAbs and enhance cell entry of HCV and infection (109).…”
Section: Figurementioning
confidence: 99%
“…Whether the humoral response plays an important role in controlling HCV infection remains controversial (105,106); indeed, the fact that hypogammaglobulinemic humans can spontaneously eradicate HCV (107) may suggest that antibody responses are dispensable. Studies showing a lack of association between neutralizing antibodies (NAbs) and viral clearance were confounded by poorly defined viral inoculum and heterogeneous patient populations.…”
Section: Figurementioning
confidence: 99%
“…This notion is further supported by the finding that the sequence of HVR1 is less variable in the absence of neutralizing antibodies. This rapidly changes, however, when neutralizing antibodies emerge, indicating evolution of viral variants in response to pressure from neutralizing antibodies (Dowd et al, 2009; Farci et al, 2000;Liu et al, 2010). Importantly, it has been shown that amino acid substitutions in HVR1 are responsible for a dramatic decrease in neutralization sensitivity over time (Dowd et al, 2009).…”
Section: Adaptive Immune Responses In Hcv-infected Humansmentioning
confidence: 99%